Didactic model of formation pedagogical universities students’ digital competence (Educational Dimension, 2020)
The article is sanctified to the analysis of problem of forming of digital competence for the students of pedagogical universities. On the basis of analysis of psychological-pedagogical researches and practical experience the didactics model of formation pedagogical universities students’ digital competence was worked out. The structural blocks of model, that in co-operation provide her integrity and functioning, are in-process certain. Destination, theoretical-methodological, semantically-judicial, control-diagnostic and result blocks behave to them. Worked out and the approved didactics model is schematic presentation of the corresponding system of work, that characterizes a hierarchy, sequence, constituents, stages and applied facilities, forms, methods and to interdependence between them and executes orientation, executive and correcting functions in organization of study of pedagogical universities of disciplines of informatics students.